In vitro comparative evaluation of cleaning efficacy and volumetric filling in primary molars: Cone beam computed tomography evaluation - Anshula Neeraj Deshpande; Neelam Hasmukhbhai Joshi; Kishan S Naik (Wolters Kluwer Medknow Publications, 2017)
Introduction: Pulpectomy of primary teeth is mostly carried out with hand files and broaches which is tricky and time consuming procedure. The development of new design features like varying tapers, non-cutting safety tips and varying length of cutting blades have resulted in new generation of rotary instruments. Aim: To compare and evaluate cleaning efficacy, canal preparation and volumetric filling using conventional files and rotary V Taper files through cone beam computed tomography. Materials and Method: Thirty extracted primary molars were selected. The teeth were randomly divided into three groups each containing 10 teeth i.e. 30 canals in each group. Group A was instrumented with K files; Group B rotary V Taper files and Group C was Hybrid group. Sodium hypochlorite (1%) was used for irrigation. Root canal filling was done with Zinc Oxide Eugenol cement in all groups. The volumetric analysis i.e. Percentage of Volume (POV) of the root canal filling in primary molars was done through CBCT Software. Result: In present study, p- value was found to be significant (<0.05). Almost 100% of canals of hybrid group were fully filled and 63.3% of canals of hand filing group were partially filled. The filling was found to be dense and no. of voids was least in hybrid group. Conclusion: Clinical time required in primary molar endodontics, especially with unpredictability and difficulty of canal morphology, is inevitable. The study confirms superior ability of rotary-file systems to shape severely curved canals with less time and significant decrease in procedural errors like partial filling, voids and inappropriate canal preparation.